Biomimetic and Electrodeposited Calcium-Phosphates Coatings on Ti - Formation, Surface Characterization, Biological Response - Pisarek, Marcin; Roguska, Agata; Marcon, Lionel; Andrzejczuk, Mariusz (IntechOpen, 2012)
None